2015
DOI: 10.1155/2015/189195
|View full text |Cite
|
Sign up to set email alerts
|

Early Vocabulary Development in Rural and Urban Mozambique

Abstract: This paper presents an adaptation of the MacArthur-Bates Communicative Development Inventories (short version) into three languages spoken in Southern Mozambique. The tool was adapted to study vocabulary development among children of 12 to 25 months of age in two communities: a rural, monolingual Changana speaking community and an urban bilingual Ronga and Portuguese speaking community. We present a norming study carried out with the adaptation, as well as a validation study. The norming study revealed various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 32 publications
2
12
1
5
Order By: Relevance
“…Beyond simply reporting the development of a measure of expressive vocabulary for school-age children, the current study's major contribution is the examination of the sources of variability in naming performance. For one, age-related differences in vocabulary acquisition were similar to what has been reported within similar (Alcock et al, 2008) and different contexts (Storms et al, 2004;Vogt et al, 2015). These age-related differences in vocabulary scores suggest that naming ability improves with maturation as children acquire more vocabulary with increased exposure.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Beyond simply reporting the development of a measure of expressive vocabulary for school-age children, the current study's major contribution is the examination of the sources of variability in naming performance. For one, age-related differences in vocabulary acquisition were similar to what has been reported within similar (Alcock et al, 2008) and different contexts (Storms et al, 2004;Vogt et al, 2015). These age-related differences in vocabulary scores suggest that naming ability improves with maturation as children acquire more vocabulary with increased exposure.…”
Section: Discussionsupporting
confidence: 71%
“…For instance, a study conducted in Madagascar concluded that among 3-to 6-year-old children, there were large differences in language development between those in the top wealth quintile and those in the lowest wealth quintile, and these differences increased as children grew older (Fernald, Weber, Galasso, & Ratsifandrihamanana, 2011). Similarly, as reported in a Mozambican study, being a female, having a mother who was educated to secondary level or higher, living in an urban area and being older were positively associated with the expressive and receptive language scores of infants (Vogt et al, 2015). The findings from these studies provide evidence that while taking into account factors that may influence child development, interventions to promote child development, and particularly language development, should begin at earlier ages and should target those who are most disadvantaged.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…So rural mothers reported their infants' vocabulary fairly accurately at both 1;6 and 2;1 years, compared to the speech the infants produced at 2;1. The 1;1 vocabulary scores were not validated, but analyses indicate that in the rural area, vocabulary at this age may be underestimated compared to our norming study (Vogt, Mastin, Aussems & Schots, 2015). So results relating to the 1;1 MBCDI should be interpreted with care, which also holds for MBCDI scores at 2;1 from the urban community.…”
Section: Methodsmentioning
confidence: 58%